Validação do camundongo rodador como modelo para surdez hereditária humana - Adriana Amorim Torres (2012)
The mutation rodador is an autosomal r `ve disorder characterized by hearing |o$ and bdance dysfunction. It was isolated in a project developed by the Laboratory of Animal and Human Genetics (ICB/UFM G, Brazil) and the Biotery of Experiments of the Department of Immunology(ICB/USP, Brazil) which aimed at inducing different mutations in the mouse genome using the mutagen N-ethyl-N-nitroscurea (ENU). Eleven mutants with phenotypx of interest were selected for genetic mapping awd positional cloning, with the aim of generating new ani ma models for human genetic di wases. Rodador mice ae characterized by circling locomotion, heai ng loss and bd ance dysfunction. Histologica analyses of the cochlea revealed abnormal stereocilia in the sensory har cells, and linkage analysis performed in recombinant animals using microsatellite markers mapped the mutation to chromosome 10, between the makers D10l\/I it17O (29.0 cM) and D10M it230 (49.0 cM ). The characterization of the region atlowed the selection of the gene Pcdh15 (Protocadheri n 15)as a strong candidate for the mutation, as it is involved with hearing function and mouse models reported for this gene present phenotypes simila to rodador. Protocadherin 15 is a calci um dependent cell adhesion protein, member of the cadherin superfamily. It is expressed in the mechawosensory hair cells in the inner ear and is a component of the extracellular filaments that control mcrphogenesis and function of stereccllia Fortyone exons and intronic flawki ng regions of the gene Pcdh15 were sequenced and an AT-to-GC transition was found in intron 23. The dtecaticn led tothe szvitch of a di nucleotide ApA for anApG on a position close to the acceptor splice site, creating a cryptic splice site within the intron. cDNA muenci ng confirmed the incorporation of 8 intronic bw into the mRNA as a resilt of the recognition of the mutated site by the spliceosome. Rea Time PCR tests revealed significantly reduced Pcdh15 transcript levels in the brain of rodador mice, in comparison to control mice. ln man, mutations in the gene PCDH15 cause heaing loss and Usher Syndrome type 1F. Rodador mouse might be a great model for hereditary hearing loss, and validation of the mutation will allow further studies on the mechanisms of heal ng function aid on the pathogenesis of the disease.